New substitute name for Sobara Oman, 1949 and recognization on Chinese Orientus species (Hemiptera: Cicadellidae: Deltocephalinae) - Xing, Ji-Chun (Zootaxa, 2017)
Oman (1949) established the leafhopper genus Sobara with Eutettix palliolata Ball, 1902 as its type species. This genus belongs to the tribe Athysanini Van Duzee, 1892 of subfamily Deltocephalinae (Hemiptera: Cicadellidae). Until now, there have been no further reports on this genus, and only one species is recorded from southwest USA.